Le régime rentier d’accumulation en Arabie saoudite et son mode de régulation - Adrien Faudot (Revue de la Régulation)
The oil export revenues contribute to the settlement of economic and institutional structures that make Saudi Arabia a prototypical rentier-state. The predominance of oil revenues, combined with socio-political parameters specific to the countries, has led the Petro-monarchy to implement a particular set of economic policies, which are analyzed here as the mode of regulation of the oil-rent-caused growth regime, rather than as gradual attempts to restrict the country’s dependence on oil. The rationalization of the Saudi rentier regime relies heavily on migrant workers and on sovereign wealth funds. The Saudi economy seems nevertheless caught up in an unstable dynamics: the country’s demographics and the mass unemployment among Saudis undermine the regime by sucking a growing share of oil revenues.